(untitled) (Bangladesh Agronomy Journal, 2022)
A pot experiment was conducted in Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during aman season, 2018 to assess the effect of biochar on rice (BRRI dhan62) under salt stress conditions. The factorial experiment was laid out in Randomized Complete Block Design (RCBD) with four replications. Three levels of salinity were used viz. Control (S0), 1600 ppm NaCl (S1), and 2800 ppm NaCl (S2) under factor A and four levels of biochar were applied viz. 0 t ha−1 (B0), 2 t ha−1 (B1), 4 t ha−1 (B2) and 6 t ha−1 (B3) under factor B. The salt materials were added on pot in two installments at 20 and 30 days after transplanting (DAT). Exposure to salinity decreased growth and yield of rice including plant height, tillers hill-1, effective tillers hill-1, grains panicle-1, 1000-grain weight, grain yield and straw yield. The magnitude of growth and yield reduction increased with increasing the salinity level. Exposure of 1600 ppm and 2800 ppm NaCl declined the grain yield of rice by 28 and 100%, respectively. Straw yield (18 and 100%, respectively) and other yield contributing parameters declined by these two levels of salinity in the same way. Application of different levels of biochar ameliorated saltinduced damages to a certain extent. Under 2800 ppm NaCl stress, application of biochar extended life duration of rice plant upto 80 DAT, whereas without biochar application rice plant died after 60 DAT. Upon exposure to 1600 ppm NaCl stress, application of 2, 4 and 6 t ha−1 of biochar increased grain yield by 37, 42 and 30%, respectively, compared with the respective salt treatments (without biochar). Biochar enhanced yield of rice under saline conditions by enhancing yield contributing attributes including effective tillers and 1000-grain weight and by reducing salt-induced damages. However, response of 4 t ha−1 of biochar was best among the biochar levels (2, 4 and 6 t ha−1 of biochar) under both saline and non-saline conditions. Bangladesh Agron. J. 2022, 25(1): 105-113